Evaluation of Insecticidal Properties of Four Essential Oils from Illicium verum, Curcuma longa, Foeniculum valgare, and Ocimum tenuiflorum against Spodoptera exigua. - Hataichanok Passara; Ammorn Insung (My University, 2021)
Abstract Four plant essential oils from Illicium verum (Star anise), Curcuma longa (Tumeric), Foeniculum vulgare (Sweet funnel), and Ocimum tenuiflorum (Holy basil) were tested against the 2 nd instar larvae of the beet armyworm, Spodoptera exigua in order to evaluate their killing efficiency, and antifeedant activity by using leaf dipping bioassay. The results revealed that the essential oils from Illicium verum and Curcuma longa were the highest effective essential oils in having killing, and antifeedant property against the insect. At 24 hours, they caused 100% mortality with only 0.750% (v/v) concentration and showed the LC50 of 0.438 and 0.413%, respectively. Both essential oils at 0.500% concentration expressed the antifeedant property at 100% within 24 hours. So that, the essential oils of Illicium verum and Curcuma longa have a potential to be applied as botanical insecticide for Spodoptera exigua control management.
Keywords: Foeniculum; Exigua; Insect Pest Control Strategies